Ionization injection effects in x-ray spectra generated by betatron oscillations in a laser wakefield accelerator. (30th March 2016) - Behm, K T; Zhao, T Z; Cole, J M; Maksimchuk, A; Mangles, S P D; Nees, J; Wood, J C; Yanovsky, V; Krushelnick, K; Thomas, A G R
Abstract: Single photon counting techniques were used with an x-ray CCD camera to measure features of synchrotron-like x-ray spectra generated by betatron oscillations of electrons in a laser wakefield accelerator (LWFA) with different injection techniques. Measurements were made using the Hercules laser system at the University of Michigan. With a single stage gas cell, we demonstrate that pure helium gas in our wakefield accelerator will produce spectra with higher critical energies than when helium mixed with nitrogen is used. This result was not evident when a two stage gas cell was used.